2014
DOI: 10.4161/bioa.29766
|View full text |Cite
|
Sign up to set email alerts
|

The role of vertebrate nonmuscle Myosin II in development and human disease

Abstract: Three different genes each located on a different chromosome encode the heavy chains of nonmuscle myosin II in humans and mice. This review explores the functional consequences of the presence of three isoforms during embryonic development and beyond. The roles of the various isoforms in cell division, cell-cell adhesion, blood vessel formation and neuronal cell migration are addressed in animal models and at the cellular level. Particular emphasis is placed on the role of nonmuscle myosin II during cardiac an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
93
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 97 publications
1
93
0
Order By: Relevance
“…NMIIB is the major NMII isoform expressed in cardiac myocytes throughout embryonic heart development (Ma and Adelstein, 2014b), although the expression of NMIIB is markedly reduced in cardiac myocytes in the first week after birth. However, there is no increase in NMIIA or NMIIC, the former being absent and the later remaining low after birth.…”
Section: Nmiib Function In Myocardial Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…NMIIB is the major NMII isoform expressed in cardiac myocytes throughout embryonic heart development (Ma and Adelstein, 2014b), although the expression of NMIIB is markedly reduced in cardiac myocytes in the first week after birth. However, there is no increase in NMIIA or NMIIC, the former being absent and the later remaining low after birth.…”
Section: Nmiib Function In Myocardial Growthmentioning
confidence: 99%
“…Three isoforms of NMII have been identified in vertebrates including humans and mice, namely NMIIA, NMIIB and NMIIC based on three different heavy chain (NMHC) genes: Myh9 encoding NMHCIIA, Myh10 encoding NMHCIIB and Myh14 encoding NMHCIIC (Golomb et al, 2004;Berg et al, 2001). Each isoform plays unique as well as overlapping roles during mouse embryonic development partially due to their differences in dynamic motor activities and expression patterns in various tissues (Ma and Adelstein, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…19 The TD is responsible for coiled-coil stability and filament nucleation or assembly, and is related to the tertiary folding structure of the tail. 4,14 The 1165th residue is thought to be located in the critical region of this bend. For these reasons, the p.R1165C mutation may induce the high frequency of deafness observed clinically.…”
Section: Discussionmentioning
confidence: 99%
“…4 Previous reports have shown that patients harboring MD mutations exhibit more severe clinical features than those with TD mutations. 5-7…”
mentioning
confidence: 99%
“…The heavy chains form a homodimer, which in a complex with two ELCs and two RLCs, is termed the myosin- II monomer. The three myosin-II isoforms exhibit different actin-activated MgATPase activities and duty ratios [812] and distinct patterns of tissue/cell expression [13,14], and they have non-redundant as well as overlapping functional roles in vivo [10,15]. …”
Section: Introductionmentioning
confidence: 99%